Association Between Index Hospitalization and Hospital Readmission in Sepsis Survivors*. Issue 3 (March 2016) - Sun, Alexander; Netzer, Giora; Small, Dylan S.; Hanish, Asaf; Fuchs, Barry D.; Gaieski, David F.; Mikkelsen, Mark E.
Abstract : Objectives: Hospital readmission is common after sepsis, yet the relationship between the index admission and readmission remains poorly understood. We sought to examine the relationship between infection during the index acute care hospitalization and readmission and to identify potentially modifiable factors during the index sepsis hospitalization associated with readmission. Design: In a retrospective cohort study, we evaluated 444 sepsis survivors at risk of an unplanned hospital readmission in 2012. The primary outcome was 30-day unplanned hospital readmission. Setting: Three hospitals within an academic healthcare system. Subjects: Four hundred forty-four sepsis survivors. Measurements and Main Results: Of 444 sepsis survivors, 23.4% (95% CI, 19.6–27.6%) experienced an unplanned 30-day readmission compared with 10.1% (95% CI, 9.6–10.7%) among 11, 364 nonsepsis survivors over the same time period. The most common cause for readmission after sepsis was infection (69.2%, 72 of 104). Among infection-related readmissions, 51.4% were categorized as recurrent/unresolved. Patients with sepsis present on their index admission who also developed a hospital-acquired infection ("second hit") were nearly twice as likely to have an unplanned 30-day readmission compared with those who presented with sepsis at admission and did not develop a hospital-acquired infection or those who presented without infection and then developed hospital-acquired sepsis (38.6% vs 22.2% vs 20.0%, p = 0.04). Infection-related hospital readmissions, specifically, were more likely in patients with a "second hit" and patients receiving a longer duration of antibiotics. The use of total parenteral nutrition ( p = 0.03), longer duration of antibiotics ( p = 0.047), prior hospitalizations, and lower discharge hemoglobin ( p = 0.04) were independently associated with hospital readmission. Conclusions: We confirmed that the majority of unplanned hospital readmissions after sepsis are due to an infection. We found that patients with sepsis at admission who developed a hospital-acquired infection, and those who received a longer duration of antibiotics, appear to be high-risk groups for unplanned, all-cause 30-day readmissions and infection-related 30-day readmissions. Abstract : Supplemental Digital Content is available in the text.